Adolescents' reactions to, and perceptions of, dissuasive cigarettes: a focus group study in Scotland. (1st November 2020) - Mitchell, Danielle; Moodie, Crawford; Critchlow, Nathan; Bauld, Linda
Abstract: The cigarette stick, as the primary form of packaging and the object of consumption, is an increasingly important marketing tool for tobacco companies. It could, however, also be used to communicate health messaging. We therefore explore adolescents' perceptions of cigarettes designed to dissuade smoking. Eight focus groups were conducted with 16–17 year-olds in Scotland ( n = 36) between November 2017 and November 2018. Groups were segmented by gender and smoking status. Participants were shown four dissuasive cigarettes; one displaying the warning 'Smoking kills'; one featuring the word 'TOXIC' and a skull and crossbones image; and two unattractively colored cigarettes (darker and lighter green). For comparison, participants were also shown a standard cigarette (white cigarette paper and imitation cork filter). All four dissuasive cigarettes were considered less attractive and more harmful than the standard cigarette, particularly among never-smokers. Some participants considered the green cigarettes to be ugly, and the on-cigarette warnings to be embarrassing and off-putting. Although reactions were mostly negative for all four dissuasive cigarettes, participants considered the on-cigarette warnings more off-putting than the green cigarettes. Participants did not generally believe that the dissuasive cigarettes would encourage cessation among established smokers, but that they may deter uptake among young people.